Selected performance indices for assessment of polypropylene susceptibility to dyeing by pigments of different UV resistance - Bieliński, Marek; Kościuszko, Artur; Smolińska, Katarzyna (Polimery, 2021)
This study presents an assessment of the effects of usage time for polypropylene (PP) experimental samples including those dyed with pigments of different UV resistance. A standard double cavity mold was used to create the samples by injection molding. Selected indices were analyzed in terms of color change (UV resistance of pigments), and UV radiation resistance of a PP polymer medium. The experiment revealed a significant impact of the accepted usage time and the type of dye concentrates on the indices characterizing the sample color change (CIELab) and a change in the structure and state of the PP medium surface.